Chácaras de lazer: um estudo sobre a vivência nas ruralidades de Guarapuava - PR - Nychai, Roseli (2012)
The aim is to indicate the resignification of spaces of Guarapuava-PR, from the characterization of townspeople`s experience in the ruralities of municipality, which is unveiled according the rhythm of national development. The townsman/townswoman seeks such type of environment as an escape way up against the urban expansion coupled with the modernization of agriculture. Process reflected in meaningful changes in the daily traditionally known, especially in the relations of production and work and between human and nature. The study was based on IBGE censuses regarding to the years 2000 and 2010, in which was identified the phenomenon of spatialization of leisure smallholdings based on the variables of homes held for occasional use in the municipality. The answering subjects of research marked the relation countryside-city, turning a new aspect into personality where the rurality exceeds the fixed character of space and appears as enclaves in the urban space. The results revealed the phenomenon already constitutes a reality with representative expansion, attracting an important part of urban population to the ruralities of municipality, over there to promote the natural local element, molding a new territorialization of this space designate as leisure and that contributes for the local development.